Participativna prenova mest - Kos, Drago (Urbani izziv, 2005)
The article consists of two parts. The first deals with the theoretical framework of urban rehabilitation. Literature provides the basis for a conclusion, which is that the key issue in rehabilitation projects is legitimate negotiation of various interests between participating individuals and institutions. In the second part this presentation and analyses of events that took place at the urban design workshop organised within the framework ofthe research project Renewal of housing estates in Ljubljana, provide experiential confirmation of the starting thesis. We established that the directly involved residents were willing to actively participate in rehabilitation procedures, however the process is never triggered, because of insufficient capacities in institutional frameworks. In conclusion several real proposals are shown, namely, how to surmount obstacles in urban rehabilitation and especially in larger housing estates built after World War 2.
Keywords: mesta; prenova; stanovanjska naselja; urbana sociologija; urbanism; urbanizem